Analisis Hukum Foto Prewedding Perspektif Sad Adz-Dzari’ah - Muhammad, Zulfan Fadhil; Sudarmaji, Waluyo; Abqori, Najih (AL-SULTHANIYAH, 2025)
The phenomenon of prewedding photography has become increasingly popular among Indonesian Muslims and has emerged as part of a new cultural practice in the sequence of events leading up to marriage. However, this practice has drawn both support and criticism from the perspective of Islamic law, particularly concerning the potential breach of sharia mandated boundaries between two individuals who are not yet in a legitimate marital bond. This study aims to analyze the legal status of prewedding photography through the lens of the kaidah Sad adz Dzari’ah, the principle of preventing actions that may lead to harm (mafsadah) or violations of sharia. It is a library research employing a qualitative approach, based on a review of classical and contemporary fiqh literature as well as an analysis of several relevant community cases.The findings indicate that the practice of prewedding photography can be classified as a form of dzarī’ah—a means that has the potential to give rise to immoral situations such as khalwat (seclusion), tabarruj (excessive display of adornment), and ikhtilāṭ (free mixing of genders)—and is therefore, in principle, prohibited under the kaidah Sad adz Dzari’ah, unless it is conducted with strict observance of sharia boundaries and appropriate supervision. These results underscore the importance of a critical and cautious mindset among Muslims when adopting popular cultural practices that are not yet fully compatible with sharia principles.